2012
DOI: 10.3390/molecules17044292
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of Hautriwaic Acid Isolated from Dodonaea viscosa Leaves

Abstract: The aim of this study was to identify an anti-inflammatory compound from D. viscosa leaves. The structure of this bioactive substance was elucidated by IR and NMR studies, which indicated that this natural product corresponds to hautriwaic acid (HA). This diterpene exhibited good anti-inflammatory activity in 12-O-tetradecanoylphorbol 13-acetate (TPA) mice ear edema models by applications at doses of 0.25, 0.5 and 1.0 mg/ear (60.2, 70.2 and 87.1% inhibition, respectively); additionally Dodonaea viscosa dichlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 19 publications
(17 reference statements)
1
39
0
Order By: Relevance
“…Hautriwaic acid (HA), a diterpene extracted from Dodonaea viscosa leaves, exhibited good anti-inflammatory activity in 12-O-tetradecanoylphorbol 13-acetate (TPA) mice ear edema models when applicated at doses of 0.25, 0.5 and 1.0 mg/ear (60.2, 70.2 and 87.1% inhibition, respectively); additionally Dodonaea viscosa dichloromethane extract (DvDE) displays a 97.8% anti-inflammatory effect at 3 mg/kg. Multiple applications of DvDE at doses of 100 mg/kg on TPA mice ear edema inhibited the edema-associated inflammation by 71.8%, while HA at doses of 15 mg/kg, reduced edema to 64% compared with indomethacin 40% [114]. Viscosine was isolated from Dodonaea viscosa, showed significant lipoxygenase inhibitory activity (IC 50 : value 39 ± 0.17), the enzyme responsible for the metabolism of the fatty acids and their metabolites eliciting inflammatory responses in the body.…”
Section: Anti-inflammatory and Analgesic Effectsmentioning
confidence: 93%
“…Hautriwaic acid (HA), a diterpene extracted from Dodonaea viscosa leaves, exhibited good anti-inflammatory activity in 12-O-tetradecanoylphorbol 13-acetate (TPA) mice ear edema models when applicated at doses of 0.25, 0.5 and 1.0 mg/ear (60.2, 70.2 and 87.1% inhibition, respectively); additionally Dodonaea viscosa dichloromethane extract (DvDE) displays a 97.8% anti-inflammatory effect at 3 mg/kg. Multiple applications of DvDE at doses of 100 mg/kg on TPA mice ear edema inhibited the edema-associated inflammation by 71.8%, while HA at doses of 15 mg/kg, reduced edema to 64% compared with indomethacin 40% [114]. Viscosine was isolated from Dodonaea viscosa, showed significant lipoxygenase inhibitory activity (IC 50 : value 39 ± 0.17), the enzyme responsible for the metabolism of the fatty acids and their metabolites eliciting inflammatory responses in the body.…”
Section: Anti-inflammatory and Analgesic Effectsmentioning
confidence: 93%
“…Although the study has not associated any of these constituents with the activities recorded, some of these bioactive constituents have been reported in previous studies to inhibit inflammation and suppress the production and release of pro-inflammatory mediators by monocytic cells. For examples, plant terpenoids have been reported to possess anti-inflammatory activities (Calou et al, 2008;Salinas-Sánchez et al, 2012;Zhang et al, 2012). Plant alkaloids have also been reported, in previous studies, to suppress inflammatory responses in rodents (Chakraborty and Brantner, 2001).…”
Section: Figure 2 Effect Of Afe On Lps-induced Tnfα Production In VImentioning
confidence: 99%
“…1) isolated from a dichloromethane extract (DCME) of D. viscosa was observed. This diterpene exhibited an anti-inflammatory effect in a model of edema in the mouse ear by 12-O-tetradecanoylforbol-13-acetate (TPA) administered topically and intraperitoneally (i. p.) [18]. Additionally, recent investigations suggested that the HA present in the methanolic extract of D. viscosa is one of the hepatoprotective constituents of this plant species [19].…”
mentioning
confidence: 99%
“…The objective of the present work was to measure the immunomodulatory effect of different doses of HA (5, 10, and 20 mg/kg) in an experimental model of RA induced by kaolin/carrageenan (K/C) injection in the right knee of mice, quantifying the levels of proinflammatory cytokines (IL-1β, IL-6, and TNF-α) and the anti-inflammatory cytokine (IL-10) in the synovial capsule of the joints of healthy and experimental, sick animals. The differences between the TPA mouse model [18] and this model of monoarthritis included that the inflammation is induced by administering carrageenan (C), based on the fact that the former generates an inflammation stimulus through the arachidonic acid cascade and the latter causes the system to establish inflammatory disease modeling [20,21]. In the research, diclofenac (Diclo) and methotrexate (MTX) were used as positive controls; Diclo possesses an NSAID mechanism in which cyclooxygenase is inhibited, and MTX modifies or alters the activity of immune-stimulated cells, decreasing their activity by inhibiting folic acid synthesis.…”
mentioning
confidence: 99%